The solar corona - Golub, Leon (Cambridge University Press, 2010)
"Intended for graduate students and astronomers seeking an introduction to coronal physics, this textbook strikes a balance between the observational and theoretical aspects of the subject. This second edition takes into account the major observational and theoretical developments of recent years to provide an up-to-date treatment of our understanding of the solar corona. After reviewing the latest observations of the solar corona, the authors explain how the studies have advanced and shaped our understanding of coronal physics. The textbook introduces a wide variety of exciting physics, including dynamo theory and radiative transfer, and shows how the transient effects of the solar cycle affect space weather. Each subject area is introduced using basic physics, and refers readers to fundamental papers on the topic, key new studies in each area, and extensive discussions in recent review articles"--Provided by publisher.